Quadruplex Negatio Invertit? The On-Line Processing of Depth Charge Sentences. (15th October 2020) - Paape, Dario; Vasishth, Shravan; von der Malsburg, Titus
Abstract: So-called "depth charge" sentences ( No head injury is too trivial to be ignored ) are interpreted by the vast majority of speakers to mean the opposite of what their compositional semantics would dictate. The semantic inversion that is observed for sentences of this type is the strongest and most persistent linguistic illusion known to the field ( Wason & Reich, 1979 ). However, it has recently been argued that the preferred interpretation arises not because of a prevailing failure of the processing system, but rather because the non-compositional meaning is grammaticalized in the form of a stored construction ( Cook & Stevenson, 2010 ; Fortuin, 2014 ). In a series of five experiments, we investigate whether the depth charge effect is better explained by processing failure due to memory overload (the overloading hypothesis ) or by the existence of an underlying grammaticalized construction with two available meanings (the ambiguity hypothesis ). To our knowledge, our experiments are the first to explore the on-line processing profile of depth charge sentences. Overall, the data are consistent with specific variants of the ambiguity and overloading hypotheses while providing evidence against other variants. As an extension of the overloading hypothesis, we suggest two heuristic processes that may ultimately yield the incorrect reading when compositional processing is suspended for strategic reasons.